The Scope of Photo-interpretation in Indian Forestry - Van, E.; Joshi, S. C. (Indian Forester, 1972)
Aerial photographs can be used in forestry for the following purposes:- 1. Mapping of forest types. 2. Stratification for sampling. 3. Direct volume estimations. 4. General planning. It has been experienced that the best use of aerial photographs in India is in mapping and stratification. The recognition of individual tree species on the aerial photographs is rather difficult and the irregular shape of many trees limits the use for direct volume estimations on the photographs. Though two economically important species of tropical forests, Tectona grandis and Shorea robusta can easily be interpreted if photographed in the right season, recognition of other species is difficult if not impossible. This means that the best approach remains a stratification of the forest in recognisable forest types and sub-stratification in height and density classes. Mapping can be done on this basis. Sampling, based on photo-stratification can gain considerable efficiency over ground methods as experienced by Pre-Investment Survey of Forest Resources Organisation in their inventory survey in East Godavari region.